2021
DOI: 10.1002/ddr.21797
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sensing receptor as a novel target for treatment of sepsis induced cardio‐renal syndrome: Need for exploring mechanisms

Abstract: Calcium sensing receptor (CaSR) is localized in various organs and plays diverse physiological and pathological roles. Several scientific contributions have suggested the involvement of this cell surface receptor in cardiac and renal diseases. Sepsis is considered to be one of the major causes of ICU admissions. Cardiac dysfunction and acute kidney injury are major manifestations of sepsis and associated with reduced survival. Presently, the treatment approaches for management of sepsis induced cardiac depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…These discrepancies of the roles of CaSR on tumor progression in different cancers imply that it might be tissue or disease specific. Interestingly, CaSR is not only expressed on tumor cells, but also exists in T lymphocytes [ 47 , 48 ]. It was found that the activation of CaSR in T lymphocytes induces the secretion of cytokines and T-cell apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies of the roles of CaSR on tumor progression in different cancers imply that it might be tissue or disease specific. Interestingly, CaSR is not only expressed on tumor cells, but also exists in T lymphocytes [ 47 , 48 ]. It was found that the activation of CaSR in T lymphocytes induces the secretion of cytokines and T-cell apoptosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The CaSR has been hypothesized to provoke glomerular damage by coupling with the TRPC6 and boosting intracellular calcium influx, which has been ascribed as one of the principal culprits in the pathophysiology of membranous nephropathy (Huang et al, 2021) and in acute kidney injuries that frequently occur in septic patients (Yadav et al, 2021). However, as the authors suggested, direct evidences on these regards are missing and, thus, further studies are needed to clarify the possible implication of the CaSR in glomerular defects under inflammatory stimuli.…”
Section: In the Kidneysmentioning
confidence: 99%
“…Intracellular calcium accumulation occurs in sepsis due to decreased uptake in sarcoplasmic reticulum and enhanced cytosolic calcium release by ryanodine receptor (Morse et al, 2017). During sepsis, cardiac dysfunction is evident due to elevated levels of calpain‐1, a calcium‐activated intracellular proteinase, which causes damage to the structural and contractile proteins dystrophin, myosin, and actin filaments of the cardiomyocytes (Celes et al, 2013; Yadav et al, 2021). The CaSR activation has been shown to elicit cardiomyocyte damage in response to lipopolysaccharide (LPS) exposure by increasing calcium release, inducing ROS production, inflammation, and apoptosis (Wang et al, 2013) A prior experimental study demonstrated the CaSR activation to be responsible for disrupting calcium balance, as observed in neonatal rat cardiomyocyte culture exposed to endotoxin LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular calcium accumulation occurs in sepsis due to decreased uptake in sarcoplasmic reticulum and enhanced cytosolic calcium release by ryanodine receptor (Morse et al, 2017). During sepsis, cardiac dysfunction is evident due to elevated levels of calpain-1, a calciumactivated intracellular proteinase, which causes damage to the structural and contractile proteins dystrophin, myosin, and actin filaments of the cardiomyocytes (Celes et al, 2013;Yadav et al, 2021) et al, 2013). Presently, there is a lack of supporting evidence in-vivo for the effects of CaSR antagonists on the development of sepsis-induced cardiac depression and its implications for shock.…”
Section: Introductionmentioning
confidence: 99%